Primate Wyszyński’s Concern for the Cultural Identity of Europe - Ireneusz Skubiś (Kościół i Prawo, 2018)
Primate Stefan Cardinal Wyszyński lived in the times of the formation of the Union, which was then called the West European Union. He recalled equal rights of all nations and peoples, while highlighting their own distinctiveness and heritage. The primate said that the common concern of the nations, especially those of Central Europe, may remind us that Europe regains its authority in the world through the Gospel and begins to inspire confidence among peoples and all continents.